Assessment of Plasma Selenium Level based on Dietary Intake among Geriatric Patients - Ika M. Silviana; Nuraini Yasmin; Ronny Lesmana (Universitas Padjadjaran, Indonesia)
Low plasma selenium level was associated with the increasing risk of death in geriatric patients, particularly those with multiple comorbidities. The sufficient level of selenium intake as an antioxidant is necessary for this population. This study aimed to investigate the plasma selenium level based on dietary intake in geriatric clinic population at Dr. Hasan Sadikin General Hospital Bandung.This study was a descriptive study using cross-sectional method. Fourteen geriatric patients were selected by consecutive sampling technique. Semiquantitative food frequency questionnaire (SQ-FFQ) was used as a tool to assess dietary intake. Plasma selenium level was measured as selenium binding protein 1 (SELENBP1) using enzyme-linked immunosorbent assay kit. Overall, mean of plasma selenium level of the subjects was 2,68 µg/L and mean of selenium intake was 62,85 µg/day. Selenium level of the subjects with sufficient selenium intake (85,7%) was 2,62 µg/L and selenium level of the subjects with deficient selenium intake (14,3%) was 3,05 µg/L. In conclusion, plasma selenium level among geriatric patients was varied and not dependent on dietary intake.Keywords: antioxidant, dietary intake, geriatric, plasma selenium level